2013
DOI: 10.1007/s11031-013-9362-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of thought-content and mood in the preparative benefits of upward counterfactual thinking

Abstract: Upward counterfactual thoughts identify how a prior outcome could have been better and have been shown to improve subsequent performance. Both the identification of corrective actions (content-specific effects) and the more general mobilization of effort as a result of negative affect (content-neutral effects) have been suggested to underlie performance benefits. The results of three experiments presented here indicate that counterfactual thoughts have broad benefits for performance, independent of their conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Indeed, Roese (1994) found that upward counterfactual thinking (U-CFT) was related to augmented intentions to perform more adaptive behaviours in the future and experimentally demonstrated that previous U-CFT did lead to a greater likelihood of actually carrying through with these intended adaptive behaviours. The finding that upward counterfactuals lead to subsequently improved performance has likewise been demonstrated in more recent studies (e.g., Myers et al, 2014). From this perspective, then, the negative affect induced by upward counterfactuals soon diminishes after a negative event, and may encourage some form of intention towards self-improvement.…”
Section: Counterfactual Thinkingsupporting
confidence: 60%
“…Indeed, Roese (1994) found that upward counterfactual thinking (U-CFT) was related to augmented intentions to perform more adaptive behaviours in the future and experimentally demonstrated that previous U-CFT did lead to a greater likelihood of actually carrying through with these intended adaptive behaviours. The finding that upward counterfactuals lead to subsequently improved performance has likewise been demonstrated in more recent studies (e.g., Myers et al, 2014). From this perspective, then, the negative affect induced by upward counterfactuals soon diminishes after a negative event, and may encourage some form of intention towards self-improvement.…”
Section: Counterfactual Thinkingsupporting
confidence: 60%
“…We argue that this specification of moderation by domain, in terms of whether the environment in which the individual operates is characterized as simple vs complex, explains the discrepancy in results between those that have shown a beneficial effect of counterfactuals on performance (Dyczewski & Markman, 2012;Markman et al, 2008;Morris & Moore, 2000;Myers et al, 2014;Reichert & Slate, 2000;Roese, 1994;Wong, 2010) vs a null effect or performance decrement (Petrocelli & Harris, 2011;Petrocelli et al, 2013Petrocelli et al, , 2012. When the domain is simple and unicausal, measuring spontaneous counterfactuals may tap variability in causal accuracy, which may or may not connect to performance.…”
Section: Simple Vs Complex Domainsmentioning
confidence: 92%
“…We emphasize that the content-specific and content-neutral pathways are not mutually exclusive but rather complementary: Both may occur at the same time, and they may interact. Nevertheless, Myers, McCrea, and Tyser (2014) provided evidence for the content-neutral pathway by using a method that held constant the content of the counterfactuals while examining the role of affect in boosting task persistence. In Study 1 of their paper, participants solved anagrams that were divided into two blocks.…”
Section: Evidence That Counterfactual Thinking Impacts Behavior: Content-neutral Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The first route, the content-neutral pathway, refers to the process by which counterfactual thinking impacts behaviors that are not relevant to a specific counterfactual. That is, regardless of counterfactual content, in this pathway, behavior changes occur mainly via negative affect (Myers, McCrea, & Tyser, 2014), enhanced motivational levels (e.g., Markman, McMullen, & Elizaga, 2008), and different cognitive procedures caused by counterfactual mindsets (e.g., Kray et al, 2009). In line with this pathway, counterfactuals can have diffuse motivational benefits by increasing negative affect and control perception (Smallman & Summerville, 2018).…”
Section: Cp and Regulatory Functions Of Counterfactual Thinkingmentioning
confidence: 89%